Pengaruh Lama Usaha dan Modal Terhadap Pendapatan dan Efisiensi Usaha Pedagang Sembako di Pasar Kumbasari - Vijayanti, Made Dwi; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 12, Desember 2016 (pp. 1347-1585), 2017)
This research was conducted in Kumbasari market. Data collection and analysis of data through questionnaires. The population in this study are all basic needs trader in Kumbasari market totaling 265 merchants. The sample used in this penlitian are as many as 73 people with the method of determination of the sample Non Probability Sampling. The analytical method used, the path analysis to determine the effect of direct and Sobel test is used to determine the indirect effect. The analysis showed that the old venture capital and directly influence revenue sembao in Kumbasari market traders. The next test, found that the old business, capital and income have a direct influence on the efficiency of basic needs trader in Kumbasari market. Variable income of an intervening variable indirect influence long effort and capital to the efficiency of basic needs trader in Kumbasari market. To increase revenue and efficiency, traders should increase entrepreneurial behavior by expanding the horizons by seeking information from various sources, both from electronic media, social media or other media.
Keywords: old business; capital; income; efficiency